1992
DOI: 10.3382/ps.0710664
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cells Expressing Immunoglobulins M and A but not Immunoglobulin G Develop an Intimate Relationship with Central Canal Epithelium in the Harderian Gland of the Chicken

Abstract: In the Harderian gland of the chicken, the epithelial and plasma cell relationships were studied by light and electron microscopy and immunohistochemical methods. In the wall of the central canal a dark epithelial cell was identified that had long branching cell processes. An anticytokeratin monoclonal antibody demonstrated that the dark cells provided an extremely large contact area for the plasma cells. Although IgM-, IgG-, and IgA-producing plasma cells were present in the Harderian gland, only IgM- and IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Since then, many researches were conducted with aim to investigate morphology and the role of this gland Khan et al, 2007;Mobini, 2012;Powell et al, 1979). Different researches showed that Harderian gland in domestic fowl participates in local immunological defence of conjunctiva and upper respiratory tract (Montgomery & Maslin, 1992;Ohshima & Hiramatsu, 2002;Olah et al, 1992;Powell et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, many researches were conducted with aim to investigate morphology and the role of this gland Khan et al, 2007;Mobini, 2012;Powell et al, 1979). Different researches showed that Harderian gland in domestic fowl participates in local immunological defence of conjunctiva and upper respiratory tract (Montgomery & Maslin, 1992;Ohshima & Hiramatsu, 2002;Olah et al, 1992;Powell et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Bar=5 μm F I G U R E 7 Apoptosis of plasma cell (arrow) with angular Russell bodies (Rb). Bar=5 μm the Harderian gland are situated IgA-, IgM-and IgG-containing plasma cells (Khan et al, 2007;Ohshima & Hiramatsu, 2002;Olah et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Olàh the plasma cells and the electron dense epithelial cells was theorized to act as an antigen presenting site for the HG (Kittner et al, 1978;Olâh et al, 1992). Olâh et al (1992) hypothesized that IgA, produced by the plasma cells in the central canal area and primary tubules, was subsequently secreted by the epithelium of the secondary tubules and acini.…”
Section: Harderian Glandmentioning
confidence: 99%